Еволюція університету у сучасному аспекті управління - Ясинська, Н. А. (Видавництво Львівської політехніки, 2013)
Прокласифіковані етапи та напрямки еволюції університету, надано характеристику кожному напряму функціонування університету в різні історичні та економічні періоди. Визначено особливості та сутність університету нового формату у сучасній моделі управління. Дослідження ґрунтується на структурно-функціональному і генетичному методах пізнання. Визначена необхідність еволюції університету у сучасних процесах управління і відкрито нові напрямки дослідження. The paper under discussion covers the classification of stages and directions of evolution of university in aspect of governance and characteristics of each direction of functioning in different historical and economic periods. Its key idea is to introduce a feature and essence of new university in the modern model of governance. The theoretical approach to the problem is based on structurally functional and genetic methods of cognition. The obtained data are given to illustrate the necessity of evolution of university in governance processes. The presented material can open new prospects for further research studies. It seems to be interesting to those who work in the field of governance and education system.
Evolution of university in the aspect of governance
Keywords: освіта; еволюція; гуманізм; ринкова економіка; управління; модель; education; evolution; humanism; market economy; governance; management; model